Morphology control of uniform CaMoO4 microarchitectures and development of white light emitting phosphors by Ln doping (Ln = Dy3+, Eu3+). Issue 12 (10th February 2017) - Laguna, Mariano; Nuñez, Nuria O.; Becerro, Ana I.; Ocaña, Manuel
Abstract : Uniform Eu 3+, Dy 3+ :CaMoO4 microarchitectures: morphology control through solvent selection and tunable photoluminescence through adjustment of doping levels. Abstract : A very simple synthesis procedure based on precipitation reactions at moderate temperature (120 °C) from solutions containing calcium nitrate and sodium molybdate, using mixed solvents (polyols and water) has been developed, which produces uniform tetragonal CaMoO4 microarchitectures with different morphologies (peanuts, cocoons, spindles and spheres) composed of self-assembled entities. The morphology and crystal size of such assemblies could be tuned by a simple change of the nature of the components of the solvent mixture or their volumetric ratio in such a mixture. All particles presented similar excitation and emission spectra arising from a charge transfer process within the MoO4 2− groups. The emitted light presented a bluish-green color and its intensity was higher for the spindle-type particles. This synthesis procedure was also suitable for doping peanut-like CaMoO4 architectures with Eu 3+ or Dy 3+ cations up to a 1% molar ratio (Ln/Ln + Ca), without altering their morphology or crystalline structure. The so prepared phosphors emitted an intense red (Eu-doped) or greenish (Dy-doped) light when excited through the MoO4 2− group excitation band, indicating the presence of an energy transfer process from such groups to the Ln 3+ cations. Finally, a white light emitting phosphor with chromaticity coordinates x = 0.335 and y = 0.365 and a correlated color temperature of 5407 K was developed by codoping peanut-type CaMoO4 particles with suitable amounts of Dy 3+ (0.35%) and Eu 3+ (0.15%) cations, which could find applications in white light emitting diodes.